DEMOCRACIA V/S AUTORITARISMO EN LA POLÍTICA LATINOAMERICANA: UN VIEJO DILEMA POLÍTICO MUY ACTUAL - Gómez Leyton, Juan carlos (Departamento de Estudos Latino-Americanos - ELA, 2018)
One of the longest and most persistent social, political and historical conflicts in the political history of "Nuestra America" societies, is the still unsolved dilemma between democratic and authoritarian political tendencies, and they were developed and expressed in these societies in different ways and at different times. The installation of transitive neoliberal democracies in most countries during the eighties showed that authoritarianism was no longer a threat to democracy. However, the various political processes that are being observed and develop today in the continent are crossed by this old but ever present conflict. Nowadays, little is discussed about the return of political, social and cultural conflicts between democratic and authoritarian tendencies. The purpose of the paper is to analyze the conflict today.